Development of Dairy Based Spread- Selection of Levels of Ultrasonication Parameters - Akshay, R; Divya K.B; S N Rajakumar; Dinker Singh; Aswin S Warrier; Shyam Suraj S; Bincy T.J (The Indian Veterinary Journal, 2024)
A study was conducted to determine the effect of ultrasonication on the sensory and physical properties of dairy based spread. The fat phase of the spread contains butter and sunflower oil. The aqueous phase constitute butter milk powder, whey protein concentrate and salt. Ultrasonication was performed using 20 kHz Ultrasonicator (Cole-Parmer, USA) at varying amplitudes (20%, 30%, and 40%) and durations (10, 20, and 30 minutes) at 40°C. The study found that certain combinations of amplitude and duration significantly influenced the quality of the fat spread. Also emulsion stability and spreadability were assessed for all treatments using modified methodologies for identifying optimal conditions for producing a superior fat spread product.